Penerapan Metode Six Sigma Dan Failure Mode And Effects Analysis (FMEA) Dalam Upaya Pengendalian Kualitas Produk STAY BKA Pada PT XYZ - Abrar Zaki Abirama Fawwaz; Ari Zaqi Al-Faritsy (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Product quality plays an essential role in maintaining the competitiveness of manufacturing companies. PT XYZ continues to experience quality issues in the STAY BKA product, with defective products accounting for 32% of total production during the Pre-Delivery Inspection (PDI) process. This study aims to analyze the defect level, identify the root causes of product defects, and propose improvement strategies using the Six Sigma and Failure Mode and Effects Analysis (FMEA) methods through the DMAIC (Define, Measure, Analyze, Improve, and Control) approach. A quantitative descriptive method was employed using production and defect data collected through direct observation and company documentation during February 2026. The results revealed five dominant defect types, namely Over Buffing (36.6%), Dent (22.4%), Bintik (20.1%), Bolong (10.5%), and Paintless (10.4%). The average Defects Per Million Opportunities (DPMO) was 59,941.91, corresponding to a process capability level of 3.0580 sigma. Fishbone analysis and FMEA indicated that the primary causes of defects were related to human, method, machine, and material factors. Improvement recommendations include installing protective partitions in WIP containers, revising standard operating procedures and buffing RPM standards, establishing standard pre-treatment duration, monitoring curing oven temperature, and scheduling regular spray gun maintenance. These improvement actions were integrated into a Control Plan supported by daily check sheets to ensure continuous quality control.